Soil density impact on soil-water characteristic curve and pore-size distribution - Dewangga, Eriko; Satyanaga, Alfrendo; Abishev, Rezat; Arinova, Anar; Muratova, Aiym; Kim, Yongmin; Kim, Jong (Frontiers in Built Environment, 2025)
In the context of climate change and urban expansion, understanding unsaturated soil behavior is critical for designing resilient infrastructure. Soil moisture retention influences stormwater management, structural performance, and the effectiveness of green infrastructure. This study focuses on the influence of soil density and water content on soil-water characteristic curve (SWCC) and soil pore-size distribution. Engineered soil from Astana, Kazakhstan, was tested under varying compaction conditions: at optimum water content (OWC), wet of optimum, and dry of optimum. SWCCs were measured using Tempe cell (0–100 kPa) and WP4C (100–300 MPa). Pore-size distributions (PSD) were derived using the Fredlund and Xing equation and analyzed with scanning electron microscopy (SEM), while mineral content was determined via X-ray diffraction (XRD). Results showed that soil compacted at OWC and dry of optimum exhibited bimodal SWCCs, while wet-compacted soil showed unimodal behavior. Increased dry density resulted in reduced air entry value (AEV) and water content, while lower density led to larger dominant pore sizes and higher matric suction. These findings offer practical insights into sustainable urban living. Understanding SWCC behavior supports the design of climate-adaptive infrastructure, such as bioretention systems, permeable pavements, and vegetated swales. Optimizing soil compaction can enhance water retention and reduce flood risk, particularly in semi-arid, climate-sensitive regions like Astana. Integrating these soil mechanics principles into urban planning contributes to long-term resilience and more sustainable city development.